Virtual Modelling and Rapid Manufacturing . - Jorge Barrtolo Paulo; Jorge Mateus Artur; Conceicao Batista Fernando; Amorim Almeida Henrique; Antonio Correia Mario; Fernandes Alves Nuno; Parente Novo Paulo; Lima Paulo; Conceicao Custodio Pedro; Goncalves Martinho Pedro; Adriano Carvolho Rui (London : Taylor & Francis, 2005)
This book contains papers presented at the 2nd International Conference on Advanced Research in Virtual and Physical Prototyping (VR@P2005), held by the School of Technology and Management of the Polytechnic Institute of Leiria, Portugal. Designed as a forum for the scientific exchange of multi-disciplinary and inter-organizational aspects of virtual and rapid prototyping and related areas, the book makes a significant contribution to developments in these fields. Drawing on the expertise of a global panel, the book's scope encompasses a wide range of topics such as biomanufacturing, materials for rapid prototyping, advanced rapid prototyping technologies, reverse engineering, and more.
Keywords: Virtual Modelling; Rapid Manufacturing .